Hubungan Tingkat Pengetahuan Ibu Hamil tentang Vitamin A dengan Pemanfaatan Makan Hati Ayam sebagai Salah Satu Nutrisi dalam Pencegahan Stunting - Inge Dewi Febri Astuti; Kristina Maharani (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The knowledge of pregnant women about nutrition plays a crucial role in the utilization of food ingredients. One of the efforts to address stunting is by consuming foods that contain vitamin A, such as chicken liver. This correlational analytical study determined the correlation between pregnant women's knowledge of vitamin A and the use of chicken liver as a nutrient in stunting prevention with a retrospective approach. The population in this study consists of pregnant women in trimester I visiting the Kedungmundu Public Health Care, with a total of 70 people. The research instruments are a cognitive level questionnaire and a food frequency questionnaire. The analysis was the Spearman Rank correlation test. This study shows that pregnant women in the Kedungmundu Health Centre area did not take chicken liver as a source of nutrition for pregnant women in preventing stunting due to low cognition about vitamin A, with a p-value of 0.047 (p-value < 0.05), indicating a strong correlation between the level of knowledge about vitamin A and the administration of chicken liver as a source of nutrition for pregnant women in preventing childhood stunting, with a very strong correlation (r = 0.257). Health education and mass media encourage pregnant women to actively expand their knowledge. The researcher anticipates that a comprehensive understanding of vitamin A's benefits will spur a rise in chicken liver consumption, thereby contributing significantly to efforts to prevent stunting